The evolving landscape of genetic biomarkers for immunotherapy in primary and metastatic breast cancer - Jin, Liang; Yang, Zijian; Tang, Wei; Yu, Pengli; Chen, Rongrong; Xu, Yan; Zhang, Jun (Frontiers in Oncology, 2025)
BackgroundMajor advances have been achieved in the characterization of primary breast cancer genomic profiles. Limited information is available on the genomic profile of tumors originating from different metastatic locations in recurrent/metastatic (R/M) breast cancer, especially in Asian patients. This study aims to decipher the mutational profiles of primary and R/M breast cancer in Chinese patients using next-generation sequencing.MethodsA total of 563 breast cancer patients were enrolled, and 590 tumor tissues and matched peripheral blood samples were collected and subjected to targeted sequencing with a panel of 1,021 cancer-related genes. The mutation spectrum, DNA damage response (DDR) genes, commonly altered signal pathways, and immunotherapy-related markers were compared between primary and R/M breast cancer. The molecular differences between our cohort and the Memorial Sloan Kettering Cancer Center (MSKCC) dataset were also explored.ResultsA total of 361 samples from primary and 229 samples from R/M breast cancer were analyzed. BRCA2, ATRX, and ATM were more frequently observed in R/M lesions among the 36 DDR genes. An ESR1 mutation and PD-L1 and PD-L2 amplification were enriched in R/M breast cancer (all p<0.05). Compared with the MSKCC dataset, we recruited more patients diagnosed at age 50 or younger and more patients with triple-negative breast cancer (TNBC) subtypes. The TNBC patients in our dataset had a higher percentage of PD-L1 amplification in metastasis tumors (p<0.05).ConclusionsThis study revealed the distinctive mutational features of primary and R/M tumors in Chinese breast cancer patients, which are different from those from Western countries. The enrichment of PD-L1 amplification in metastatic TNBC indicates the necessity to re-biopsy metastatic tumors for immunotherapy.